(untitled) (Research, Society and Development, 2021)
Historically, Brazil has privileged the road transport modal as a result of policies adopted mainly during the 20th century, which developed and encouraged the use of motorized and private transport, which is one of the pillars for the development of problems with urban mobility. Another pillar that aggravates this problem is the process that cities have been developing. With rural exodus, the slum process was intensified and the lack of public policies to develop adequate infrastructure for this portion of the population, brought the aggravation of current locomotive problems in Brazil. Brazilian cities have peripheral neighborhoods that are largely dependent on the central regions, generating large displacements and, consequently, difficulties in adapting all this transshipment along limited routes with insufficient structure for the demand. As a more economical solution for this, mixed zoning should be applied using the concept of an active facade in these regions dependent on the urban center. With this application, it would reduce the portion of the population that would need services and commerce in distant regions, consequently, reducing urban displacement problems. In addition to providing relief from mobility problems, mixed zoning is financially a more viable solution in relation to infrastructure works in the urban road network and construction of new modes of transport, which can be used in all urban centers, regardless of population size.